AN ANALYSIS OF STRATEGIES FOR OPTIMIZING LAND AND BUILDING TAX REVENUE IN INCREASING REGIONAL OWN-SOURCE REVENUE IN THE REGIONAL FINANCE AND INCOME MANAGEMENT AGENCY OF SUKABUMI CITY - NURUL LEILA; IKE RACHMAWATI; ERRY SUNARYA (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
Land and building tax is one of the potential Regional Own-Source Revenues that can contribute to regional Original Income; therefore Land and Building Tax revenue must be strived for optimally. However, based on the initial data that the researchers obtained, it was unfortunate that Land and Building tax revenue in Sukabumi City had not been optimal when compared to the actual potential land and building taxes. The realization rate of Land and Building Tax revenue when compared to the Potential Land and Building tax in Sukabumi City for a period of three years, namely 2018, 2019 and 2020 only reached 79.19%, meaning that almost 20% of Land and building Tax in Sukabumi City was still a tax that had been in arrears and had not been paid by taxpayers. Clearly this was a fairly crucial problem and required to be resolved immediately. In this journal, the researcher would seek to analyze the correct strategy that could be applied in an effort to optimize Land and Building Tax Revenue having the research location was the Regional Technical Implementing Unit (UPTD) of Regional Income Management. The research used qualitative descriptive research method with the key resource person was the Secretary of the Regional Financial and Income Management Agency, Mr. Olga Pragosta, S.H, M.M and the main resource person was the head of the UPTD of Regional Income Management, as well as several accompanying source persons. In the research, the researcher applied the SWOT analysis method to map the internal Strengths and Weaknesses of the UPTD as well as the external opportunities and threats encountered by the UPTD. The mapping was intended to formulate the correct strategy that can be applied as an effort to optimize land and building tax revenue. With the application of those strategies, it was expected that the performance of the UPTD of Regional Income Management, especially in optimizing the Land and Building Tax could be better and in accordance with one of the missions of the UPTD of Tax and Building Management, namely: Optimizing revenue with measurable intensification and extensification according to economic growth as well as increasing local revenue and PBB-P2 & BPHTB sectors.